1986
DOI: 10.1002/neu.480170502
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular transmission in an insect visceral muscle

Abstract: The electrical properties of the muscles of locust oviduct have been examined using intracellular recordings. The muscle cells are both dye and electrically coupled. They possess a wide array of spontaneous electrical activity ranging from slow oscillations of membrane potential to action potentials. In addition to possessing spontaneous electrical activity, certain regions of the oviduct are under motor control. The amplitude of evoked excitatory junction potentials (EJPs) increased step wise revealing innerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…2). We have previously demonstrated that the innervation to locust oviducts is confined to the common oviduct and lower lateral oviduct terminating at the insertion of the ovarioles (see Lange et al, 1984a;Orchard and Lange, 1986). The upper lateral oviducts, into which the ovarioles insert are not innervated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2). We have previously demonstrated that the innervation to locust oviducts is confined to the common oviduct and lower lateral oviduct terminating at the insertion of the ovarioles (see Lange et al, 1984a;Orchard and Lange, 1986). The upper lateral oviducts, into which the ovarioles insert are not innervated.…”
Section: Resultsmentioning
confidence: 97%
“…The third preparation included the lower lateral and common oviducts that have previously been shown to be the innervated region (see Fig. 3; Lange et al, 1984a;Orchard and Lange, 1986). All three preparations were maintained under saline and pharmacological agents were applied by removing a known volume of saline and replacing with an equivalent volume of saline containing the test substance.…”
Section: Bioassaysmentioning
confidence: 99%
“…Our data, together with growing evidence for cotransmission at other invertebrate (e.g., refs. [18][19][20][21][22][23] as well as vertebrate (e.g., refs. 24-26) muscles, reinforce the idea that synapses can transmit complex chemical signals that may fine tune the response of the postsynaptic cell.…”
Section: Discussionmentioning
confidence: 99%
“…Selective diffusion of octopamine into the CNS or ovaries could not only explain the achieved rescue but could also explain the enhanced ability of octopamine versus tyramine feeding to suppress the dTdc2 RO54 sterility phenotype (Table I). In other insects, octopamine relaxes ovarian muscles to allow the release of mature eggs into the oviducts (32,33). In the locust Locusta migratoria, this occurs via activation of octopamine-2B receptors, which leads to a rise in cAMP (34).…”
Section: Expression Of Either Dtdc1 or -2 In A Dtdc2-specific Patternmentioning
confidence: 99%